Fuzzy dichotomy versus traditional dichotomy between spoken and written language. Typing in WhatsApp - Giraldo, Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article aims to destabilize the traditional dichotomy between spoken and written language of texts realized in an oral manner in WhatsApp on the basis of traditional criticisms. To do so, the category fuzzy dichotomy was created as a method, which applies a logical and linguistic analysis to this Saussure’s classical linguistics distinction. One of the main findings was that the traditional dichotomy between spoken and written language is unclear and it disappears when typing in WhatsApp. Three resulting figures served to explain the interpretation that dilutes the Saussurean dichotomy of spoken and written language, and to present the fuzzy dichotomy recognizing the intersection of elements between writing and speaking. It is concluded that typing in WhatsApp blurs the boundaries between spoken and written language and it positions itself as a new linguistic and communicative phenomenon.